Kentucky's graduated driver licensing program for young drivers: barriers to effective local implementation. Issue 4 (1st December 2001) - Steenbergen, L C; Kidd, P S; Pollack, S; McCoy, C; Pigman, J G; Agent, K R
Abstract : Objectives —To examine the implementation of graduated driver licensing (GDL) in Kentucky and to use the data collected to recommend actions to enhance the effectiveness of the GDL program. Methods —Data were acquired from surveys of 700 law enforcement officers and more than 40 judges and from interviews with 100 persons who implement or are affected by Kentucky's GDL program—for example, traffic court judges, licensing clerks, law enforcement officers, insurance agents, driving instructors, parents, and employers of teens. Transcripts from interviews were analyzed using a qualitative data analysis computer program. Results and conclusions —Participants noted a widespread lack of awareness of the night-time driving restriction and a substantial number of young drivers receiving little driving time during the learner permit phase. It appeared that specific GDL provisions can be difficult for judges and law officers to enforce and the penalty of license suspension after several traffic violations may not be a sufficient deterrent. Efforts are needed to increase parental awareness of GDL provisions, GDL purpose, and their teen's traffic violations and to increase parental enforcement of restrictions that are difficult for law enforcement agencies to monitor, such as the night-time driving restriction and the adult supervision requirement.